Spectroscopic Characteristics For Rhodamine C Tincture in Diverse Solvents - K. S. Rida; J. A. Kathum; S. I. Ibrahim (Engineering and Technology Journal, 2017)
The article included calculating the quantum aptitude and Radiative emission probability, Radiative life time, and fluorescence life time of Rhodamine C with fixed concentration (5*10-5 mol/l) in some solvent ( Distilled water, Methanol, Ethanol, 2-Propanol, Dichloromethane, Ethyl acetate, Dimethyl formamide) which differ in their polarity.There is a slight change in the crest of the absorption which showed up at wavelength (555-560 nm), the red shift was about (16-23 nm) of RC dye in different solvent.